KEBIJAKAN PEMERINTAH TERHADAP PENANGGULANGANKEMISKINAN DALAM PROGRAM PENGEMBANGAN KECAMATAN (PPK) DI SULAWESI SELATAN - Sahade, Sahade (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This study aims to determine the extent of District Development Program (DDP) contribution in reducing poverty in South Sulawesi and the supporting and inhibiting factors for DDP in reducing poverty in Jeneponto Regency. To prove this research, the analytical tools used are the tabulation method on the respondent's statement, and the criteria range as a category measure to identify the extent to which the respondent's view of an object. The results showed that: 1) The implementation of DDP activities received good responses from various circles of society, especially in villages / sub-districts as indicated by the results of data analysis where DDP activities had an influence on poverty alleviation. 2) The implementation of DDP activities not only seeks to alleviate poverty but also seeks to carry out training activities in efforts to develop village community businesses. It is proven from the results of data analysis showing good responses where there is an influence on community business development. 3) As for the constraints in the field is the limited time, funds and field extension personnel so that implementation in the field is still not optimal